If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + -5n + 11 = 2 + -3n + 9 Reorder the terms: 11 + 2n + -5n = 2 + -3n + 9 Combine like terms: 2n + -5n = -3n 11 + -3n = 2 + -3n + 9 Reorder the terms: 11 + -3n = 2 + 9 + -3n Combine like terms: 2 + 9 = 11 11 + -3n = 11 + -3n Add '-11' to each side of the equation. 11 + -11 + -3n = 11 + -11 + -3n Combine like terms: 11 + -11 = 0 0 + -3n = 11 + -11 + -3n -3n = 11 + -11 + -3n Combine like terms: 11 + -11 = 0 -3n = 0 + -3n -3n = -3n Add '3n' to each side of the equation. -3n + 3n = -3n + 3n Combine like terms: -3n + 3n = 0 0 = -3n + 3n Combine like terms: -3n + 3n = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 4x+25=29 | | 2x+8+x=-12-2x | | -9k=2.34 | | y^4-25y^2+144=0 | | 4(4+3x)=136 | | 8x=48 | | 3(x-5)=3+x | | 12y-3=16y-9y | | 2Y+19=23 | | 4x^2-13x+7=8x+2 | | t^2+t=2 | | x^2+4x+p=0 | | 3x-9=1+x | | 6(6+7x)=456 | | 4(-18-2)-5*18=1 | | -2x-1/2=x/5 | | (2x+3)+(x-6)=90 | | 2+2-4+3-7+8= | | -6n+15=-5n-1 | | 2(4-5x)+9=2x-23-8x | | 7(6x+7)=91 | | 5+6x=3+5x-8 | | 3x=2x-17.5 | | 2x/5-2x-1/2=x/5 | | 5*6+5x+6x=30x | | 7(8+x)=98 | | 4(x+3)+28=-4x | | -3x-8=5y+32 | | 6x=4y+8 | | (5x-2)(2x+7)= | | 4(y+3)=3y+13 | | 8(7-x)=4(3x-16) |